A theology of the built environment : justice, empowerment, redemption - Gorringe, Timothy (Cambridge University Press, 2002)
This is the first book to reflect theologically on the built environment as a whole. Drawing on a wide range of both theological and social-scientific sources, Tim Gorringe explores Christianity in its urban settings, focusing on the use of space, design, architecture, and town planning to make a theological critique.